2012
DOI: 10.3390/toxins4111120
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Deoxynivalenol Toxicity Mechanisms: The Brain as a Target

Abstract: Deoxynivalenol (DON), mainly produced by Fusarium fungi, and also commonly called vomitoxin, is a trichothecene mycotoxin. It is one of the most abundant trichothecenes which contaminate cereals consumed by farm animals and humans. The extent of cereal contamination is strongly associated with rainfall and moisture at the time of flowering and with grain storage conditions. DON consumption may result in intoxication, the severity of which is dose-dependent and may lead to different symptoms including anorexia,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 101 publications
2
81
0
2
Order By: Relevance
“…In vivo studies have shown that DON affects the activity of brain neurons, particularly in relation to anorexia and emesis; exposure of pigs to 10–75 or >150 µg of DON/kg BW (body weight)/day causing partial/total feed refusal or vomiting, respectively (for review: [153]). Importantly, higher doses of DON are required in mice, i.e ., 0.5 to 5 mg/kg of BW causing anorexia, suggesting that pigs are more sensitive to brain effects than mice [153].…”
Section: Pathophysiological Effects Of Donmentioning
confidence: 99%
“…In vivo studies have shown that DON affects the activity of brain neurons, particularly in relation to anorexia and emesis; exposure of pigs to 10–75 or >150 µg of DON/kg BW (body weight)/day causing partial/total feed refusal or vomiting, respectively (for review: [153]). Importantly, higher doses of DON are required in mice, i.e ., 0.5 to 5 mg/kg of BW causing anorexia, suggesting that pigs are more sensitive to brain effects than mice [153].…”
Section: Pathophysiological Effects Of Donmentioning
confidence: 99%
“…DON exerts a range of toxic effects in mammals and humans, e.g., on the intestine, the immune system and the brain [2,3]. The effects on the brain have been linked to the observed emesis and feed refusal in pigs [2].…”
Section: Introductionmentioning
confidence: 99%
“…DON exerts a range of toxic effects in mammals and humans, e.g., on the intestine, the immune system and the brain [2,3]. The effects on the brain have been linked to the observed emesis and feed refusal in pigs [2]. Conjugation of DON with L-glutathione (GSH) was recently shown to be a biotransformation pathway in wheat plants that were injected with DON in controlled trials [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, the Joint Food and Agriculture Organization/ World Health Organization (FAO/WHO) Expert Committee on Food Additives (JECFA) proposed a provisional maximum tolerable daily intake (PMTDI) for DON of 1 µg/kg body weight (bw) based on the growth effects associated with DON exposure (8,27,28). In the following decade, investigations into the mechanisms of the effect of DON on weight gain were pursued and understood (8,9,(29)(30)(31)(32). In 2010, JECFA extended the PMTDI to apply to both DON and its acetylated derivatives and concluded that mean estimates of national exposure to DON were below the PMTDI of 1 µg/kg bw (8,27,28).…”
Section: Introductionmentioning
confidence: 99%